Conectividade do conhecimento ecológico local entre os pescadores artesanais de camarão: direcionamento e influências na produtividade pesqueira - Castro, Rafael Barros de (2020)
Artisanal shrimp fishing is of socio-economic and cultural importance, especially in developing countries. To enable the sustainable exploitation of resources, maintain social well-being and respect culture and tradition in the activity, it is necessary that this fishery has a management compatible with its profile, which in the region is artisanal in medium and small scale. To support knowledge and make management politically viable, local ecological knowledge (LEK) of fishermen is a relevant instrument, but rarely used. The present study aims to investigate which profiles of fishermen are best connected through LEK, and whether these fishermen form groups with LEK themes. For this evaluation, interviews were carried out by accidental sampling with artisanal shrimp fishers, using semi-structured forms as instruments in three coastal regions in north-eastern Brazil. Linear regression and the Gephi program were used to assess the fisher’s connectivity on LEK. The results show that LEK on reproduction and migration are predominant for fishers and that there is a refinement of the LEK as experience increases. Groups of fishermen connected through LEK themes were also registered. The reproductive aspects and migration of the three main species of shrimp are the most declared to be known by fishers. It is concluded that the LEK is not homogeneous among the fishers, being essential to consider these differences in order to improve the process of decision making and management of artisanal fisheries. A communication channel among stakeholders may be developed taking LEK as a path, mainly through the themes of reproduction and migration, helping the effectiveness of fisheries management of marine shrimps for their productive and sustainable use. The dialogue would improve fishers well-being and achieving the objectives of the interested groups.